1991
DOI: 10.1021/j100169a039
|View full text |Cite
|
Sign up to set email alerts
|

A subcritical Hopf bifurcation in the methylene blue oscillator: effects of imposed fluctuations

Abstract: plexed to either the solvent or the electrode surface (or both). There is no evidence from the PMV data to suggest that surface effects are responsible for the long lifetime of the intermediate. It is, however, possible that the estimated lifetime is that of the nitrilium ion formed by reaction of acetonitrile with the diphenylmethyl cation provided that the nitrilium ion is electroactive (presumably by dissociative reduction to form the radical and acetonitrile).It is possible to estimate the potential for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…However, as stated previously, our biofilm oscillations start with nonzero amplitude. This is suggestive of a subcritical Hopf bifurcation, also commonly observed in natural systems (32)(33)(34). In this case, the limit cycle born at the bifurcation is unstable, overlapping in parameter space with the stable steady state.…”
Section: A Dde Model For Biofilm Stress Dynamicsmentioning
confidence: 54%
“…However, as stated previously, our biofilm oscillations start with nonzero amplitude. This is suggestive of a subcritical Hopf bifurcation, also commonly observed in natural systems (32)(33)(34). In this case, the limit cycle born at the bifurcation is unstable, overlapping in parameter space with the stable steady state.…”
Section: A Dde Model For Biofilm Stress Dynamicsmentioning
confidence: 54%
“…Effects of Visible Light on Oscillations and Turing Structures. The behavior of the Methylene Blue−sulfide−oxygen oscillator under CSTR conditions is well-known from experimental and numerical work. , No work, however, has been done to study the effect of light on the oscillations in the MBO. During our examinations of Turing patterns we found that light affected the pattern formation process (described below), and it thus was obvious to study the light effect on oscillations, too.…”
Section: Resultsmentioning
confidence: 99%
“…In chemical reaction systems, both theoretical and experimental studies have revealed the effects of external fluctuations on the nonlinear dynamics. Periodic modulations by light, flow rates, or electrical current have been found to induce entrainment, ,,,,, resonance, ,, and chaos. Stochastic perturbations applied to flow rates have lead to bursting oscillations in the methylene blue oscillator, sustained oscillations in the glycolysis of yeast, and convergence of chaos in a model of the Belousov−Zhabotinsky (BZ) reaction. , …”
Section: Introductionmentioning
confidence: 99%